The financial status and factors affecting personal well-being among urban poor in Kuala Lumpur - Moga Dass, Thinagaran; Sabri, Mohamad Fazli (Secholian Publication PLT, 2017)
The main purpose of this study is to understand the financial status of urban poor community in Kuala Lumpur and factors affecting their personal well-being. The sampling size of this research is 1,064 respondents chosen by using systematic sampling method. The data was obtained by using self- administered questionnaires and the data being analysed by descriptive analysis meanwhile and multi regression analysis. The results shows that the urban poor community in Kuala Lumpur are having a moderate level of financial literacy possess a less effective financial behaviour, experiencing a high financial strain and adapting a moderate level of personal well-being. Besides that, the results also indicates that the financial literacy has no influence on personal well-being of the urban poor community, meanwhile financial behaviour has a positive influence and financial strain has a negative influence on the personal well-being of the urban poor community. The findings of the study suggest the government and non-government organisation such as Economic Planning Unit ((EPU), Kuala Lumpur City Hall (KLCH or DBKL), Central Bank of Malaysia (BNM), Credit Counselling and Debt Management Agency (CCDM or AKPK), Federation of Consumer Association (FOMCA) to make an inclusive effort and approach to improve the personal well-being of the urban poor. By understanding more about the financial status of the urban poor community, it is hoped to help them to become financial prudence and in the long-run could lead them into a good decision making while facing conflicts in financial issues and maintain a good quality of life. It is important to ensure the urban poor consumers have better financial management skills which lead them to make the right decision in order to enhance their personal well-being.